CLIMATE-FOCUSED USER EXPERIENCE (UX) DESIGN: LEVERAGING ADOBE EXPERIENCE CLOUD FOR SUSTAINABLE ENGAGEMENT - `, Bhargav Reddy Piduru (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2023)
The article delves into the scope, objectives, methodologies, and key findings of leveraging Adobe Experience Cloud to enhance climate-focused User Experience (UX) design. The primary focus of the study is to underscore the pivotal role played by UX design in fostering climate awareness and encouraging sustainable behaviors through the Adobe Experience Cloud platform. Through an in-depth exploration of the project's parameters, goals, research approaches, and significant discoveries, this abstract highlight the critical connection between effective UX design and its potential to drive positive environmental impact and promote lasting sustainable engagement. In summary, this article sheds light on the symbiotic relationship between Climate-Focused User Experience Design and Adobe Experience Cloud, demonstrating how their synergy can effectively promote climate awareness and sustainable behaviors. The study's scope, objectives, methodologies, and key findings collectively underscore the immense potential of UX design to serve as a catalyst for positive change, contributing to a more environmentally conscious and responsible society.